2019
DOI: 10.1016/j.joca.2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β signaling in intervertebral disc health and disease

Abstract: Objective: This paper aims to provide a comprehensive review of the changing role of transforming growth factor-b (TGF-b) signaling in intervertebral disc (IVD) health and disease. Methods: A comprehensive literature search was performed using PubMed terms 'TGF-b' and 'IVD'. Results: TGF-b signaling is necessary for the development and growth of IVD, and can play a protective role in the restoration of IVD tissues by stimulating matrix synthesis, inhibiting matrix catabolism, inflammatory response and cell los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
85
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 112 publications
1
85
1
Order By: Relevance
“…TGFβ3 has been shown to maintain the phenotype of disc cells in organ culture by elevating the levels of activated ERK1/2, which can regulate the expression of TGFβRI and TGF‐β‐RII . Activation of ERK1/2 also suggests that TGFβ could potentially signaling through the non‐canonical pathway . However, it is also possible that TGFβ could exert an anabolic effect via activation of SMADS2/3 …”
Section: Discussionmentioning
confidence: 99%
“…TGFβ3 has been shown to maintain the phenotype of disc cells in organ culture by elevating the levels of activated ERK1/2, which can regulate the expression of TGFβRI and TGF‐β‐RII . Activation of ERK1/2 also suggests that TGFβ could potentially signaling through the non‐canonical pathway . However, it is also possible that TGFβ could exert an anabolic effect via activation of SMADS2/3 …”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of LBP is poorly understood, intervertebral disc degeneration (IVDD) has been proposed to be the major cause of LBP 2,3 . IVDD is characterized by increased oxidative stress, the degradation of extracellular matrix (ECM) and apoptosis, and decreased autophagy or mitophagy 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the activity of MMPs is not limited to matrix cleavage; they also modulate the in ammatory response [27], which may explain why degenerative discs were also sensitive to pro-in ammatory stimuli [28]. It has been reported that TGF-β was a major up-stream regulator of collagens and proteoglycans [29]. However, TGF-β gene transcription was not affected in this study.…”
Section: Discussionmentioning
confidence: 49%